CREATINE KINASE QUANTITY IN HIGH INTENSITY ACUTE RESISTANCE TRAINING AND BORG SCALE (Fiep Bulletin - online, 2014)
Introduction: Markers of muscle damage are often used to check the effectiveness of the training. Aim: The aim of this study was to identify if there is elevation of the quantity of creatine kinase (CK) in high intensity acute resistance training and if the effort´s subjective perception scale is able to identify the intensity of this exercise. Methodology: 20 health males were selected with age between 53,9±8 anos. These were subdivided into two different groups. One of the groups did the protocol training of acute resistance exercise at 60% and the other at 75% of the maximum load. At the end of the protocol the participants answered the Borg scale. Blood samples were collected 30 minutes before the training and ten minutes after. To the biochemical analysis it was used the kinetic colorimetric method. Kolmogorov-Smirnov was done to check the normality of the sample. Student T test was done. It was adopted p
Keywords: creatine kinase; resistance training; muscle proteins.